Penerapan Model Logistik Fraksional dalam Memproyeksikan Jumlah Penduduk di Kabupaten Indramayu Tahun 2025-2030 - Lu’lu Nurzahra; Isnu Aji Saputro Isnu; Noor Sofiyati (UJMC (Unisda Journal of Mathematics and Computer Science), 2026)
The continuous growth in population necessitates accurate projections as a foundation for regional development planning. This study aims to apply a fractional logistic model employing the conformable fractional derivative to project the population of Indramayu Regency for the period 2025–2030. The research was conducted using population data from Indramayu Regency spanning the 2020–2024 period, with two fractional orders, namely α = 0,8 and α = 0,2, each comprising four model variations. The accuracy of the models was evaluated using the Mean Absolute Percentage Error (MAPE). The findings indicate that Model III with a fractional order of α = 0.8 yields the highest accuracy, with a MAPE value of 0.121669%. Based on this model, the population of Indramayu Regency is projected to increase from 1,943,094 inhabitants in 2025 to 1,991,027 inhabitants in 2030. The results demonstrate that the conformable fractional logistic model is capable of providing population projections with excellent accuracy, thereby offering a potential alternative for population-data-based development planning.